A Comparative Analysis of Vibrio cholerae Contamination in Point-of-Drinking and Source Water in a Low-Income Urban Community, Bangladesh - Ferdous, Jannatul; Sultana, Rebeca; Rashid, Ridwan B.; Tasnimuzzaman, Md.; Nordland, Andreas; Begum, Anowara; Jensen, Peter K. M. (Frontiers in Microbiology, 2018)
Bangladesh is a cholera endemic country with a population at high risk of cholera. Toxigenic and non-toxigenic Vibrio cholerae (V. cholerae) can cause cholera and cholera-like diarrheal illness and outbreaks. Drinking water is one of the primary routes of cholera transmission in Bangladesh. The aim of this study was to conduct a comparative assessment of the presence of V. cholerae between point-of-drinking water and source water, and to investigate the variability of virulence profile using molecular methods of a densely populated low-income settlement of Dhaka, Bangladesh. Water samples were collected and tested for V. cholerae from 'point-of-drinking' and 'source' in 477 study households in routine visits at 6-week intervals over a period of 14 months. We studied the virulence profiles of V. cholerae positive water samples using 22 different virulence gene markers present in toxigenic O1/O139 and non-O1/O139 V. cholerae using polymerase chain reaction (PCR). A total of 1463 water samples were collected, with 1082 samples from point-of-drinking water in 388 households and 381 samples from 66 water sources. V. cholerae was detected in 10% of point-of-drinking water samples and in 9% of source water samples. Twenty-three percent of households and 38% of the sources were positive for V. cholerae in at least one visit. Samples collected from point-of-drinking and linked sources in a 7-day interval showed significantly higher odds (P < 0.05) of V. cholerae presence in point-of-drinking compared to source [OR =17.24 (95% CI = 7.14–42.89)] water. Based on the 7-day interval data, 53% (17/32) of source water samples were negative for V. cholerae while linked point-of-drinking water samples were positive. There were significantly higher odds (p < 0.05) of the presence of V. cholerae O1 [OR = 9.13 (95% CI = 2.85–29.26)] and V. cholerae O139 [OR = 4.73 (95% CI = 1.19–18.79)] in source water samples than in point-of-drinking water samples. Contamination of water at the point-of-drinking is less likely to depend on the contamination at the source. Hygiene education interventions and programs should focus and emphasize on water at the point-of-drinking, including repeated cleaning of drinking vessels, which is of paramount importance in preventing cholera.